EDUKASI LIMA PILAR PADA DIABETASI DI WILAYAH KERJA PUSKESMAS SUAK RIBEE KECAMATAN JOHAN PAHLAWAN KABUPATEN ACEH BARAT - Ridha Fitri; Khairunnisak Khairunnisak; Rolas Nentya (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Diabetes Mellitus (DM) is a chronic metabolic disease characterized by hyperglycemia due to abnormalities in insulin secretion and action. The prevalence of DM in the Suak Ribe Community Health Center (UPTD) area was the second highest (731 cases) in 2024. The objective of this community service is to improve patient knowledge and independence in implementing the Five Pillars of Diabetes Management to achieve optimal glycemic control. The implementation methods include Medical Nutrition Therapy (3J principle), physical activity guidance, pharmacological therapy education, and self-monitoring of blood sugar. This program was implemented on April 16–17, 2026, followed by an evaluation on April 20, 2026. The pre-test results showed that community knowledge of the Five Pillars of Diabetes Management was in the sufficient category (44.4%). After the implementation of the activity, the post-test results proved that participants' understanding of the application of the five pillars of DM management increased (94,4%). This indicates that the intervention carried out by the community service team is very effective in improving patient health literacy. In conclusion, increased knowledge and good understanding are expected to encourage patient independence in controlling blood sugar levels.